Відповідність податку на додану вартість в Україні до вимог Євросоюзу - Аполлонова, Надія Віталіївна (НТУ "ХПІ", 2016)
Досліджується відповідність податку на додану вартість в Україні до вимог Євросоюзу, вказуються розбіжності та основні проблеми податку на додану вартість. Проводиться аналіз змін, які наступили в ході адаптації законодавства України до вимог Євросоюзу. Зроблено висновки щодо відповідності податку на додану вартість України до вимог Євросоюзу та запропоновано шляхи оптимізації та адаптації.

The compliance of the value-added tax in Ukraine with the requirements of the European Union is investigated, the differences and the main problems of the value-added tax are indicated. An analysis of the changes that have occurred during the adaptation of Ukraine's legislation to the requirements of the European Union is being analyzed. The list of requirements put forward by the European Council is given to countries that have expressed a desire to become members of the European Union. The example of administration and levying of the value-added tax of the leading countries, as well as their methods of combating fraud in the implementation of budgetary compensation for value-added tax, is given as an example. Conclusions have been drawn about the compliance of Ukraine's value-added tax with the requirements of the European Union and proposed ways of optimization and adaptation.
Consistency value added tax in Ukraine with the EU requirements
Keywords: декларація; бюджет; відшкодування; директива; ПДВ; declaration; budget